2022
DOI: 10.1155/2022/4037240
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Intervention Effect of Music on Insomnia of College Students

Abstract: In this study, we have analyzed the intervention effect of music on insomnia of college students. For this purpose, we have selected college students of grade 2019 facing insomnia in our school and randomly selected 96 of them as research objects after the informed consent of the students. 96 subjects were randomly divided into two groups, observation group and control group, 48 cases in each group. No music intervention was applied to the control group, while music intervention was applied to the observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…As a non-pharmacological intervention, listening to music (Jespersen et al, 2022) has been recommended as one of the sleep quality promotion modalities by the American Sleep Association (Gradisar et al, 2013). Several studies have shown a significant effect of music on improving sleep quality (Yamasato et al, 2020), increasing sleep satisfaction (Dos, 2022), and reducing depression (Harmat et al, 2008) in college students. However, some studies reported that music could not affect objective sleep quality (Lazic and Ogilvie, 2007;Messineo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a non-pharmacological intervention, listening to music (Jespersen et al, 2022) has been recommended as one of the sleep quality promotion modalities by the American Sleep Association (Gradisar et al, 2013). Several studies have shown a significant effect of music on improving sleep quality (Yamasato et al, 2020), increasing sleep satisfaction (Dos, 2022), and reducing depression (Harmat et al, 2008) in college students. However, some studies reported that music could not affect objective sleep quality (Lazic and Ogilvie, 2007;Messineo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%